The founding and first dynamics of the peruvian society of international law: between american hegemony and the pacIfic problem (1913-1928) - Nieto Minaya, Willy Felix Edgardo (2025)
The present article examines the dynamics and the role played by the Peruvian Society of International Law (PSIL) in its early years within the diplomatic and legal context of the region. The hypothesis suggests that during this period, the SPDI was influenced by two interrelated dynamics: the rise of the United States as a regional hegemony and Peru’s efforts to find a solution to the Pacific problem and the return of Tacna and Arica. In this logic, the United States established different Societies of International Law as a mechanism of continental legal power, and Peru joined this trend through the PSIL, finding in American initiatives various coincidences with its own Peruvian objectives in legal matters, which could help solve its border problems with Chile between the years 1913-1928.